The gastric response to a transpyloric duodenal tube. Issue 10 (October 1975) - Longstreth, G F; Malagelada, J R; Go, V L
Abstract : The quantification of gastric, pancreatic, biliary, and small bowel functions in man often requires the use of intestinal tubes. In this study, the presence of a transpyloric tube did not alter gastric emptying, acid secretion, or serum gastrin levels in response to an ordinary solid meal.